Basic engineering for medics and biologists : an ESEM primer - Lee, T. Clive; Niederer, P. (Peter) (Studies in health technology and informatics, 2010)
Developments in bioengineering and medical technology have led to spectacular progress in clinical medicine. As a result, increased numbers of courses are available in the area of bioengineering and clinical technology. These often include modules dealing with basic biological and medical sciences, aimed at those taking up these studies, who have a background in engineering. To date, relatively few participants from medicine have taken up courses in biomedical engineering, to the detriment of scientific exchange between engineers and medics. The European Society for Engineering and Medicine (E.